10-Second Demos: Boiling Asynchronous Online Instruction Down to the Essentials with GIF Graphics. Issue 3 (1st October 2016) - Aleman, Karla J.; Porter, Toccara D.
ABSTRACT: Connecting with text-weary students can be a challenge in the online instructional environment. Librarians have often developed screencast videos and integrated screenshots into online learning objects to teach students basic research skills. An alternative technology, graphical interchange format (GIF), may prove to be an excellent blend of the two media. GIF technology allows librarians to reach visual learners by producing continuously looping animated images. Librarians at two academic libraries recently incorporated GIFs into online learning modules and research guides to experiment with the technology and its accessibility. This article will explore GIF technology's place in the current landscape of online library research instruction. The authors will provide their recommended best practices for incorporating GIFs as online learning objects with a spotlight on accessibility. The authors will expound upon their discoveries in working with the technology and describe the advantages and challenges of using such a technology to demonstrate research skills.